Drugs and the Efforts to Overcome it in Jayawijaya Regency - Telly Nancy Silooy; Girinius Wenda (LPPM UNAIM, 2021)
The widespread circulation of drugs in the community and the magnitude of the adverse effects and losses, both economic losses and social losses caused by it, have opened awareness from various circles to drive a